2020
DOI: 10.3390/nano10081540
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen- and Oxygen-Containing Three-Dimensional Hierarchical Porous Graphitic Carbon for Advanced Supercapacitor

Abstract: Three-dimensional hierarchical porous graphitic carbon (HPGC) were synthesized via one-step carbonization-activation and a catalytic strategy. The method can not only improve the graphitization degree of carbon materials, but also offer plentiful interfaces for charge accumulation and short paths for ion/electron transport. Polypyrrole, potassium hydroxide, and nickel acetate were used as the carbon precursors, activating agent, and catalyst, respectively. The retraction and dissolution of Ni caused the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…As presented in Figure 4 , it is shown that the NiS/A-PVP-NC was wetted immediately, while the NiS/PI-NC resisted the electrolyte, as highlighted by the white circle. Although the high nitrogen content increases wettability [ 53 ], the oxygen-containing functional groups and porous structures deliver more significant contributions [ 41 , 54 , 55 ]. As a result, the NiS-A-PVP-NC possessed superior wettability, with a 6 M KOH electrolyte, than the NiS/PI-NC.…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Figure 4 , it is shown that the NiS/A-PVP-NC was wetted immediately, while the NiS/PI-NC resisted the electrolyte, as highlighted by the white circle. Although the high nitrogen content increases wettability [ 53 ], the oxygen-containing functional groups and porous structures deliver more significant contributions [ 41 , 54 , 55 ]. As a result, the NiS-A-PVP-NC possessed superior wettability, with a 6 M KOH electrolyte, than the NiS/PI-NC.…”
Section: Resultsmentioning
confidence: 99%
“…Agro-based precursors such as sucrose [5], glucose [6], fructose [7], common sugar [8], ligno-cellulosic biomasses like bio-refinery residue [9], furfural manufacture waste [10], tamarind wood [11], willow bark [12], olive pomace [13], etc. Besides there are reports on carbonization of polymeric materials such as polypyrrole [14], polymer blends like poly(acrylonitrile)/poly(vinylidene Fluoride) [15] and co-polymers like poly(aniline-co-p-phenylenediamine) [16], etc. have been converted to carbons and used in applications such as adsorbents for environmental remediation [17], secondary batteries such as lithium-and sodium-ion batteries, etc.…”
Section: Introductionmentioning
confidence: 99%